Effect of Adding Black Soldier Fly Larvae Flour to Rations on Broiler Chicken Performance - Ndun, Alberth Nugrahadi; Mulik, Simon Edison; Nguru, David Agustinus; Menoh, Yori Raimona (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aims to evaluate the effect of adding Black Soldier Fly (BSF) larvae flour to the ration on feed consumption, body weight gain, and feed conversion in poultry. The four treatments used were P0 (ration without the addition of BSF flour), P1 (ration + 5% BSF flour), P2 (ration + 10% BSF flour), and P3 (ration + 15% BSF flour), with each treatment repeated four times. The livestock used in this study were 80 broiler chickens, which were distributed in each treatment unit of 5 chickens each. This study used a Completely Randomized Design (CRD) and data were analyzed using Analysis of Variance (ANOVA), with Duncan's further test if there was a significant effect. The results showed that the P3 treatment with the addition of 15% BSF flour produced the lowest feed consumption (1063.44 grams) and the best feed conversion (0.9818), indicating higher feed efficiency. In contrast, the P0 treatment without the addition of BSF flour had the highest feed consumption (1482.20 grams) and the lowest feed conversion (2.5832). Body weight gain increased significantly with increasing proportion of BSF flour, namely P3 had the highest body weight gain (1087.95 grams) compared to other treatments. From the results of this study, it can be concluded that the addition of BSF flour up to 15% in the ration has a positive effect on the growth and performance of broiler chickens. The best results for the observed parameters were feed consumption (1063.44 grams), with feed conversion (0.9818), and the best body weight gain (1087.95 grams). The use of BSF flour in poultry rations shows potential as an efficient alternative feed ingredient. Further research is recommended to explore the long-term effects and potential for commercial application.